Determining sample size balancing power, precision, and practicality - Dattalo, Patrick (Oxford : Oxford University Press, 2008)
This text describes the following available approaches for estimating sample size in social work research and discusses their strengths and weaknesses: power analysis; heuristics or rules-of-thumb; confidence intervals; computer-intensive strategies; and ethical and cost considerations.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Sampling (Statistics); Social sciences -- Statistical methods; Social surveys -- Methodology